E-LEARNING AND STUDENT ATTITUDES: AN ANALYSIS OF ATTITUDES IN ONLINE LEARNING OF THE QUR'AN HADITH - Syahmidi, Syahmidi; Surawan, Surawan (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study was to determine students' attitudes towards the learning process of web-based e-learning as well as the constraints and solutions of online learning using web-based e-learning for Al-Qur'an Hadith subjects. This research uses mixed methods. The subjects in this study were students of class XI MA Raudhatul Jannah Palangka Raya. The data in this study were collected through questionnaires, interviews and documentation. Data validation used source triangulation and percentage tabulation, while data analysis used data reduction, data presentation and verification. The results of this study indicate that 1) students' attitudes towards online learning using e-learning in the Qur'an Hadith subject students' attitudes towards online learning using web-based e-learning in the Qur'an Hadith subject are good ( 65%.) 2) Obstacles in learning include networking and difficulty understanding the material. While the solution is to find a strong network, look for other references, provide alternatives in collecting assignments and always provide stimulus to students.